Humanitarian intervention and the responsibility to protect: deconstructing regional legal and theoretical frameworks for action in Africa - Iyi, John-Mark (My University, 2014)
The ECOWAS and AU peace and security legal frameworks have attracted little study amongst international law scholars despite its far-reaching normative innovations and implications for Africa, the UN Charter-based law of humanitarian intervention and international law in general. With the exception of a couple of writers, the few studies that exist have dismissed such provisions as article 4(h) of the AU Constitutive Act and article 10 and 25 of the ECOWAS Mechanism for Conflict Prevention, Management, Resolution Peacekeeping and Security Protocol (MCPMRPS) as illegal treaties because of their incompatibility with articles 2(4), 24(1), 53(1) and 103 of the Charter. None of these studies examined the theoretical basis of these treaties and at a time the world is in search of a legal framework for the operationalisation of the Responsibility to Protect (R2P), it has become imperative to undertake an interrogation of the theoretical underpinnings of these treaties. My study tested the legal validity of the AU/ECOWAS intervention instruments using two theoretical frameworks: transformations of world constitutive process of authoritative decision and the illegal international legal reform theories. It also examined the validity of the treaties under conventional and customary international law. The thesis advanced three main arguments: First, I argued that there are four constitutive processes in the international legal order. The UN was designed to establish a system with effective hierarchical institutions of decision making where unilateral acts would be unnecessary and so illegal. The UNSC failed in its duty as the authoritative decision-maker saddled with the responsibility of maintaining international peace and security and protecting human rights. On this basis the unilateral interventions treaties established by AU/ECOWAS are valid. Secondly, I argued that in a legal system such as the UN Charter-based system that poorly approximates justice and where there are few prospects for legal reform, a unilateral act of illegal international legal reform aimed at bringing about moral improvement in the law is permissible. The AU/ECOWAS treaties constitute illegal international legal reform because they seek to improve the law of humanitarian intervention to prevent future mass atrocities. Thirdly, I argued that under treaty law, there are several grounds for holding the AU/ECOWAS laws valid, basically because they constitute treaty-based interventions for which UNSC authorization is not required. I conclude that the fundamental assumptions on which the Charter was based have been radically altered and African states can plead change of v circumstances to obviate the application of the full weight of the Charter framework. Based on the above conclusions, I proposed the AU/ECOWAS treaty regimes for a theory of regional responsibility to protect as a theoretical framework for the operationalisation of the R2P in Africa.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Law, 2014.